A comparative study of inotropes and vasopressin in critical care unit - Bhise, Pranjali P.; Gawali, Pravin F.; Sugriv, Dhakne G.; Tokale, Rohit; Bhambre, Akshay S. (International Journal of Research in Medical Sciences, 2025)
In critical care, inotropes and vasopressin are key agents for addressing hemodynamic instability. This article evaluates their effectiveness, safety, and clinical outcomes in conditions like septic shock, cardiogenic shock, and post-cardiac arrest syndrome. Inotropes such as dobutamine and epinephrine enhance cardiac performance but may pose risks like arrhythmias and increased myocardial oxygen consumption. Vasopressin, acting as a non-catecholamine vasopressor, promotes vasoconstriction without significantly impacting heart rate or myocardial contractility, often complementing catecholamine therapy to reduce their dosage requirements. Studies indicate vasopressin can lower the reliance on high-dose catecholamines and may decrease cardiovascular complications, though further investigation is needed in specific groups, such as patients with kidney impairment. The discussion underscores the importance of tailoring treatment to individual patient needs and stresses the necessity for more research to refine dosing strategies and identify response predictors. This review supports clinicians in improving the management of critically ill patients with circulatory challenges.